To create or to recall original ideas: Brain processes associated with the imagination of novel object uses. (February 2018) - Benedek, Mathias; Schües, Till; Beaty, Roger E.; Jauk, Emanuel; Koschutnig, Karl; Fink, Andreas; Neubauer, Aljoscha C.
Abstract: This fMRI study investigated what brain processes contribute to the generation of new ideas. Brain activation was measured while participants generated new original object uses, recalled original object uses, or recalled common object uses. Post-scan evaluations were used to confirm what ideas were newly generated on the spot or actually retrieved from memory. When compared to the recall of common ideas, the generation of new and old original ideas showed a similar activation pattern including activation of bilateral parahippocampal and mPFC regions, suggesting that the construction of new ideas builds on similar processes like the reconstruction of original ideas from episodic memory. As a difference, the generation of new object uses involved higher activation of a focused cluster in the left supramarginal gyrus compared to the recall of original ideas. This finding adds to the converging evidence that the left supramarginal gyrus is crucially involved in the construction of novel representations, potentially by integrating memory content in new ways and supporting executively demanding mental simulations. This study deepens our understanding of how creative thought builds on and goes beyond memory.